Conservationland: Toward the anthropology of professionals in global nature conservation. (December 2018) - Kiik, Laur
When reading anthropological writings on global nature conservation, one may wonder: Where are the conservationists? Anthropologists have written nuanced ethnographies of how native people encounter and are dispossessed by transnational environmental NGOs and conservation policies. Yet, anthropologists have neglected the other side of those worldwide encounters: the conservation practitioners. Instead, conservationists are sometimes misrepresented as homogenous, impersonal and voiceless. This is surprising, considering anthropologists' increasing interest in cultures of expertise, including that of professionals in international development. This paper contributes to building the anthropology of professionals in global biodiversity conservation. It locates and reviews disparate material on conservationists from across the ethnographic literature. It argues for attending to the perspectives and diversity of conservation professionals and institutions, their transnational social worlds, naturalist worldviews and emotional lives. A section discusses the key contradictory positionality of the Global South's local-national professionals. Lastly, the paper reflects on practical challenges to fieldwork in 'Conservationland'.